Training Needs Assessment for Teaching Obstetric Point-Of-Care Ultrasound (O-POCUS) and Postpartum Hemorrhage (PPH) Management; A Case of Nursing, Clinical Medicine, Radiography and Imaging Sciences Departments in Keny - Mutua, Caleb; ichalai, Alex; Mutua, Felix; Mwaura, Catherine; Wafula, David; Kinyua, Kennedy (African Journal of Education and Practice, 2025)
Purpose: This study aims to assess the preparedness of faculty in the Nursing, Clinical Medicine, and Radiography and Imaging Sciences departments in Kenya to teach Obstetric Point-of-Care Ultrasound (O-POCUS) and Postpartum Hemorrhage (PPH) management, in light of the 2024 National Guidelines requiring structured training in these areas. The purpose is to identify training gaps among educators and propose solutions to improve maternal health outcomes. Methods: A descriptive cross-sectional design with a quantitative approach was employed to gather data from health educators using a structured self-administered questionnaire. The survey targeted tutors and clinical instructors across the three departments. The questionnaire, aligned with the 2024 O-POCUS guidelines, covered areas such as training gaps, resource availability, teaching methods, and institutional readiness. Data were analyzed using SPSS, with descriptive statistics and chi-square tests used to identify relationships between various factors. Findings: The study revealed significant gaps in faculty training and resources. In the Nursing and Clinical Medicine departments, over 80% of educators had not received training in O-POCUS, and 60% in PPH management. The Radiography and Imaging Sciences department showed a similar trend, with 89% of respondents reporting a lack of training in both areas. Additionally, limited access to ultrasound machines and teaching materials hindered effective teaching. Respondents favored hands-on workshops, mentorship, and simulation-based scenarios as the most effective teaching methods. Curriculum inclusion of O-POCUS and PPH management was inadequate across all departments, with many respondents uncertain or unaware of its integration. Unique Contributions to Theory, Policy and Practice: The study concluded that faculty members in the Nursing, Clinical Medicine, and Radiography and Imaging Sciences departments are inadequately trained to teach O-POCUS and PPH management, leading to gaps in student preparedness. Despite strong leadership support, there is insufficient resource allocation and curriculum integration of these critical topics. This lack of preparation impacts the quality of maternal healthcare education and hinders the implementation of effective practices in obstetric emergencies. To address these gaps, it is recommended that a comprehensive faculty development program be implemented, focusing on both theoretical knowledge and hands-on training in O-POCUS and PPH management. Curricula across all departments should integrate these topics with clear guidelines and balance between theory and practical application. Institutions must prioritize resource allocation, including the provision of portable ultrasound machines, phantoms, and standardized teaching materials.